Micro-Climatic Study of Pigeonpea [Cajanus cajan (L.) Millap.] Genotype Under Variable Weather Conditions - Singh, Ajit; Mishra, S. R.; Singh, A. K.; Mishra, A. N. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted during kharif season of 2012 at Agrometeorological Research Farm of N.D. University of Agriculture and Technology Kumarganj, Faizabad (U.P). The treatment comprised of three sowing dates viz., July 06th, July 16th and July 26th were kept as main plot and three varieties viz., Narendra Arhar-1, Narendra Arhar-2 and Bahar were kept as sup-plot. The results revealed that sowing on July 06th produced significantly higher growth, yield attributes and yield of pigeon pea due to fulfilment of optimum thermal requirement for various plant processes. Lowest seed yield was observed under late sown (July 26th) condition due to higher temperature during reproductive stage. July 26th reduced the crop duration by 23 days over sowing on July 16th and 10 days over sowing done on July 06th. Thermal use efficiency was recorded significantly highest in late sown condition (July 06th). Narendra Arhar-2 variety was highest thermal efficient as it intercepted highest solar radiation for growth, development and yields. Relationship between accumulated GDD and LAI of pigeonpea sown on July 06th revealed that LAI increased with increase of accumulated GDD up to 2000 °C days (R2=0.85). Accumulated GDD and dry matter accumulation of pigeon pea sown on July 06th was linearly correlated with accumulated GDD (R2=0.95) indicating that dry matter increased with increase of accumulated GDD. Seed yield was decreased linearly with increase of canopy temperature and it decreased by 45 kg with every increase of 1 °C canopy temperature.